Study of breastfeeding practices and problems among postnatal mothers: a hospital based study - Mise, Pooja J.; Mise, Aditya J.; Mise, Sangamesh J.; Siddappa, Margol (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Breastfeeding has many health and developmental advantages for infant and mothers. Breastfeeding remains the simplest, healthiest and least expensive feeding method that fulfils the infant’s needs. Methods: 112 mothers having infants of age group less than 1 year were included in the study. Self-administered questionnaire was used to collect information on breastfeeding practices in the initial six months of birth of the child. Study population were postnatal mothers in KIMS Hubli, Hospital IPD and OPD. Results: 112 lactating mothers were included in the study. Majority of subjects 86 (76.7%) were in the age group 21-30 years. About 43 (38.4%) lactating mother initiated breast feeding practices within 1 hour after the delivery. 63.4% of the infants received exclusive breast feeding. Lactation failure 40% and unsatisfactory growth of baby 50% were the main reasons for early weaning. Most common cause of delay in initiation in breast were caesarian section and delivery complication (53.12% and 21.88% respectively) Only 27 (24.1%) babies were given pre-lacteal feed. Conclusions: There is a need of giving information regarding breast feeding during antenatal visits to inform the mothers regarding proven facts of advantages of exclusive breastfeeding, as undesirable cultural practices such as giving pre-lacteals, late initiation of breast feeding are still prevalent among the community and these should be discouraged. For successful feeding, mothers need active support, care and privacy during pregnancy and following birth, not only of their families and communities but also of the entire health system.